Perlindungan Hukum Terhadap Pejabat Notaris Yang Membuat Perjanjian Perkawinan Selama Perkawinan Berlangsung - Muhtar, Achmad; Rato, Dominikus; Dwi Anggono, Bayu (Prodi Hukum S1 - Fakultas Hukum - Universitas Pamulang, 2024)
Initially, the marriage process begins with a marriage agreement or what is called a pre-nup. The academic anxiety that can be found is related to the issue of marriage agreements, namely that there is a conflict of norms. This is indicated by the Constitutional Court's decision in its decision confirming that notary officials are given the authority to ratify marriage agreements. Meanwhile, in Law Number 2 of 2014 concerning Amendments to Law no. 30 of 2004 concerning the Position of Notaries, where in this law there are no provisions governing the authority of a notary to ratify marriages made by the parties during the marriage period, so that notary officials do not have a strong legal reason as a basis for making a marriage agreement. The problem formulation in this research is First, What is the Essence of a Marriage Agreement according to Positive Law in Indonesia? Second, what is the form of legal protection for notary officials in Marriage Agreements made after marriage? Third, how can the formulation of a marriage agreement made during the marriage period provide legal certainty? The method used is the normative juridical method. The results of this research are that a marriage agreement was made before and during the marriage. Apart from that, if there is no prior marriage agreement, then the original assets or assets acquired during the marriage do not have permission for those assets (joint assets). Apart from that, the notary is authorized to make an agreement if it must comply with the terms of the validity of the agreement and if it does not comply with the terms of the validity of the agreement it will be canceled by the judge. This can certainly provide legal certainty for notaries.